A trust-region approach for computing Pareto fronts in multiobjective optimization - Mohammadi, A. (2024)
Funding Information: This work was funded by national funds through FCT - Fundação para a Ciência e a Tecnologia I.P., under the scope of projects PTDC/MAT-APL/28400/2017, UIDP/00297/2020, and UIDB/00297/2020 (Center for Mathematics and Applications). The work of the first author was additionally supported by the scholarship 2020.08249.BD, also granted by FCT - Fundação para a Ciência e a Tecnologia I.P.. Publisher Copyright: © 2023, The Author(s).